2021
DOI: 10.1093/femsec/fiab013
|View full text |Cite
|
Sign up to set email alerts
|

Composition of seagrass phyllosphere microbial communities suggests rapid environmental regulation of community structure

Abstract: Recent studies have revealed that seagrass blade surfaces, also known as the phyllosphere, are rich habitats for microbes; however, the primary drivers of composition and structure in these microbial communities are largely unknown. This study utilized a reciprocal transplant approach between two sites with different environmental conditions combined with 16S rRNA gene sequencing (iTag) to examine the relative influence of environmental conditions and host plant on phyllosphere community composition of the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…All of these findings indicated that the local environmental conditions could be another significant factor in shaping the foliar microbial community of wild soybeans. Our results are consistent with earlier studies ( Vogel et al, 2021 ). In general, the microbial communities colonizing the same host species and/or organs could be filtered and selected by environmental conditions, such as temperature, heat, and precipitation, which could directly shape the foliar microbial community ( Jiao et al, 2019 ; Chen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…All of these findings indicated that the local environmental conditions could be another significant factor in shaping the foliar microbial community of wild soybeans. Our results are consistent with earlier studies ( Vogel et al, 2021 ). In general, the microbial communities colonizing the same host species and/or organs could be filtered and selected by environmental conditions, such as temperature, heat, and precipitation, which could directly shape the foliar microbial community ( Jiao et al, 2019 ; Chen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Considering the microbial constituents in seagrass restoration is likely even more important when using transplants from other regions, or transplants grown in ex situ nurseries, especially, as we show that microbial communities can differ over comparatively small spatial scales (<10 km). If microbes are not considered it is possible that transplants could be maladapted to their new environments, or suffer from transplantation shock (Wang et al, 2021) which could be a contributing factors leading to restoration failure (Vogel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms, which are often the most abundant group within systems, play a crucial role in material and energy cycling ( Tarquinio et al., 2019 ; Lemay et al., 2021 ; Nguyen et al., 2022 ). Due to their short life cycles, rapid community turnover, and sensitivity to the environment, they are excellent subjects for investigating community assemblage ( Vogel et al., 2021a , Vogel et al., 2021b ). Seagrass bed ecosystems are known for their highly diverse habitats and host abundant microbial communities, providing habitats for various marine organisms and numerous ecosystem services ( Yarnall et al., 2022 ; Han et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%